Preschool children’s resource allocation towards and reasoning about exclusion of agents with disabilities - Landwehrmann, Teresa; Paulus, Markus; Christner, Natalie (Cognitive development, 2024)
How to act fairly among individuals with different abilities is a challenge for societies that subscribe to principles of inclusivity and individual rights. This raises the question whether children acknowledge the needs of others with a disability and how they reason about inclusive group-decisions. This study examined whether 3- to 6-year-old children distribute resources unequally benefitting others with physical or behavioral disabilities and how children reason about their distributions. Also, we investigated children’s decisions and justifications on whether individuals with a disability should participate in group activities even when an authority suggests otherwise. Results showed that preschoolers see disability as a reason for equitable distribution and advocate for inclusion even against an authority’s suggestion. This means that when asked to allocate resources, children take the needs of individuals with disabilities into account. Our findings indicate that children consider inclusion as a moral concern. •Children rectify functional impairments by allocating needed resources equitably.•Older preschoolers justify unequal distributions with impairments of recipients.•Children endorse inclusion of disabled protagonists against authority’s suggestion.•Preschoolers refer to considerations of equality when they advocate for inclusion.